The political situation in Iraq, and the problem of Kurdish autonomy in 1960-1970 - Baigarayev N. А. (Journal of Oriental Studies, 2016)
This article addresses problems of Kurdish autonomy and the ways of its resolving in the context of the situation in Iraq in 1960-1970 on the basis of historical juridical documents.